Social mobilization. - Rogers, Todd.; Goldstein, Noah J.; Fox, Craig R.
This article reviews research from several behavioral disciplines to derive strategies for prompting people to perform behaviors that are individually costly and provide negligible individual or social benefits but are meaningful when performed by a large number of individuals. Whereas the term social influence encompasses all the ways in which people influence other people, social mobilization refers specifically to principles that can be used to influence a large number of individuals to participate in such activities. The motivational force of social mobilization is amplified by the fact that others benefit from the encouraged behaviors, and its overall impact is enhanced by the fact that people are embedded within social networks. This article may be useful to those interested in the provision of public goods, collective action, and prosocial behavior, and we give special attention to field experiments on election participation, environmentally sustainable behaviors, and charitable giving. -- (from the author)
Keywords: Social influence; Collective action; Charitable giving; Voter mobilization; Environmental behavior; Field experiments